ANALISIS PENDAPATAN DAN KELAYAKAN USAHA PENJUALAN AYAM RAS PEDAGING DI PASAR MASOMBA KOTA PALU - D. Kamarudin , Afandi, Trisna (AGROTEKBIS, 2015)
Broiler is one of livestock producing meat which is most in demand by people, because it is one of the animal source of protein and is relatively cheaper.Broiler meat consumption is always greater than thatof otherpoultry, specially in Palu City. Broiler marketing in Palu City certainly involves traders to distribute the broiler from thefarmer directly to the end consumer.The traders in Palu City use the market to market the broiler.The greatest number of broiler traders in Palu City exist at Masomba Market, yet they are faced by some problems,namely marketing cost and price.The research was aimed for determining how muchincome earned and knowing feasibilityof Broiler Tradein Masomba Market.The research had been conducted in Masomba Market at Palu City from April to May 2014.The respondents were all broiler traders selling in Masomba Market. Sampling method was done through cencus. The number of respondents was 16 broiler traders.The analysis used in this study were Income Analysis and Feasibility Analysis.The findingsrevealed that the amount ofincomeearned by the trader was Rp3.156.581permonth.Based on the feasibility analysis, Revenue of Cost of Broiler Trade obtainedwas 1.23.It means that Broiler Trade in Masomba Market is reasonable to dobecause R/C > 1.